Implementation Of The Child Protection Act As A Positive Law In Eradicating Child Marriage In Indonesia - Baby Suryani Fithri; Windy Sri Wahyuni; Ariman Sitompul (IHSA Institute, 2022)
In the application of the Marriage Act diamana has determined that the minimum age for marriage is 19 (nineteen) years for men and women. However, there are still many people who practice marriage with minors age 19 (nineteen). The practice of child marriage can be caused by a variety of factors, and has many negative impact on children. The Covid-19 pandemic is one of the causes of the increase number of child marriages in Indonesia. This study uses normative juridical Law Research methods, based on Written regulations and literature studies that examine aspects, theories, structure, and legal explanations relating to this study. The data used is secondary data obtained from literature studies. The approach used in this study is the statutory approach. Ada Child Protection Law which became the legal umbrella in the eradication of child marriage in Indonesia, but on the other hand, there are still many challenges in reducing the number of child marriages practices, one of which is the regulation related to the dispensation of marriage and incessant the criminal act was committed under the guise of child marriage.